2009
DOI: 10.1016/j.ijfoodmicro.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Physiological traits of Penicillium glabrum strain LCP 08.5568, a filamentous fungus isolated from bottled aromatised mineral water

Abstract: Penicillium glabrum is a ubiquitous fungus distributed world wide. This fungus is a frequent contaminant in the food manufacturing industry. Environmental factors such as temperature, water activity and pH have a great influence on fungal development. In this study, a strain of P. glabrum referenced to as LCP 08.5568, has been isolated from a bottle of aromatized mineral water. The effects of temperature, a(w) and pH on radial growth rate were assessed on Czapeck Yeast Agar (CYA) medium. Models derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 40 publications
5
45
0
3
Order By: Relevance
“…However, these results do agree with physiological studies of bacterial and fungal pure cultures, indicating that these microbial groups differ in their responses to pH. Fungal species typically have a wide pH optimum, often covering 5-9 pH units without significant inhibition of their growth (Wheeler et al, 1991;Nevarez et al, 2009). The available evidence for the fungal pH relationship thus indicates a significantly weaker direct connection with pH than bacteria (Beales, 2004), although pure culture studies have shown preference for certain pH values for different taxa of soil fungi (Domsch et al, 1980).…”
Section: Discussionsupporting
confidence: 68%
“…However, these results do agree with physiological studies of bacterial and fungal pure cultures, indicating that these microbial groups differ in their responses to pH. Fungal species typically have a wide pH optimum, often covering 5-9 pH units without significant inhibition of their growth (Wheeler et al, 1991;Nevarez et al, 2009). The available evidence for the fungal pH relationship thus indicates a significantly weaker direct connection with pH than bacteria (Beales, 2004), although pure culture studies have shown preference for certain pH values for different taxa of soil fungi (Domsch et al, 1980).…”
Section: Discussionsupporting
confidence: 68%
“…The maximum xylanase production has already been reported at a temperature range of [25][26][27][28][29][30] C by Trichoderma viride 28 and P. glabrum. 29 Usually, the maximal reported temperature for these filamentous fungus is 35 C, with an indication of the absence of growth 37 C. 30,31 The activity of lignocellulolytic enzymes also increased on increasing the agitation up to 100 rpm. As for the submerged fermentation, mechanical agitation is known to be a crucial factor because of its effectiveness in mixing the contents of the medium, uniform air distribution and prevention of cell clumping.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme production was carried out at different pH (4-6) when incubated at a different temp. (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) C) for 24-120 h at 50 ¡150 rpm based on the Central Composite Design (CCD) of RSM (Table 4 and Table 1). An aliquot of fermentation broth was withdrawn from the flask after a regular interval and centrifuged at 4 C at 7000 rpm for 15 min.…”
Section: Growth Conditions and Enzyme Production Set Upmentioning
confidence: 99%
“…The first response area was observed for the less intense thermal shock conditions 30 C:120 min to 40 C:10 min and revealed an increase of fungal growth in comparison with the fungal biomass of the control T96. A clear fungal growth increase was measured for the lowest shock condition (30 C:120 min) at supra-optimal temperature (Nevarez et al 2009). A second area was observed for intermediate thermal conditions (40 C:230 min, 40 C:120 min or 47 C:42 min), which showed a moderate reduction in fungal biomass compared to the T96 control but still greater than the fungal growth of the T48 control.…”
Section: Effect Of Thermal Shock On Fungal Growthmentioning
confidence: 93%
“…The strain has been registered as LMSA 1.01.421 in the Brittany Microbe Culture Collection (Souchothèque de Bretagne; University of Brest, France; www.ifremer.fr/souchotheque) and as LCP 08.5568 in the fungal collection of the Laboratory of Cryptogamy at the Museum National d'Histoire Naturelle (Paris, France; www.mnhn.fr). The cardinal (minimum, optimum and maximum) growth conditions of temperature and pH for this filamentous fungus have been estimated to be 6.6 C, 24.3 C and 33.8 C and pH 0.50e1.00, pH 5.50 and pH 11.20 (Nevarez et al 2009). …”
Section: Fungal Strain and Culture Mediummentioning
confidence: 97%